Exercise-induced modulation of gut microbiota in individuals with obesity and type 2 diabetes: a systematic review and meta-analysis - Lin, Weian; Pu, Lei; Qian, Xingyu; Pan, Jinchen; Cheng, Ruiqi; Sun, Peng (Frontiers in Microbiology, 2025)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the effects of exercise on gut microbiota in individuals with obesity and type 2 diabetes (T2D), including alpha-diversity indices (Shannon, Simpson, Chao1, and observed OTUs) and taxonomic composition, to explore the potential role of gut microbiota in mediating the effects of exercise on disease progression.MethodsA total of 19 studies comprising 1,062 participants were included. Alpha-diversity indices and taxonomic changes were analyzed using meta-analysis and qualitative synthesis. Subgroup analyses were conducted based on exercise type and age.ResultsMeta-analysis showed that exercise significantly increased the Shannon index in both the obesity group (SMD = 0.40 [0.15, 0.65], P = 0.002) and the T2D group (SMD = 0.48 [0.08, 0.88], P = 0.02). No significant changes were observed in the Simpson index or observed OTUs. The Chao1 index showed a significant improvement in individuals with obesity (SMD = 0.45 [0.06, 0.85], P = 0.03). Subgroup analyses indicated that combined exercise produced more pronounced effects than aerobic exercise alone in both the obesity group (SMD = 0.42, P = 0.02) and the T2D group (SMD = 0.69, P = 0.04). Younger individuals (<50 years) were more responsive to exercise interventions (Obesity: SMD = 0.32, P = 0.027; T2D: SMD = 0.86, P = 0.003). Qualitative synthesis revealed consistent enrichment of butyrate-producing taxa (notably Roseburia and Faecalibacterium prausnitzii) and Akkermansia muciniphila, while responses of the Firmicutes/Bacteroidetes ratio and genus-level taxa such as Prevotella and Bacteroides varied across studies.ConclusionExercise significantly enhances gut microbiota diversity in individuals with obesity and T2D, with combined exercise showing potentially greater benefits. Younger populations may respond more effectively to exercise interventions. Future research should further investigate the effects of personalized exercise strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251015520, identifier CRD420250653594